To solve the equation \( 729^{4x-1} = 9^{3x+8} \) using the laws of exponents, we can first express both sides in terms of powers of the same base.
We know:
- \( 729 = 9^3 \)
- Therefore, \( 729^{4x-1} = (9^3)^{4x-1} = 9^{3(4x-1)} = 9^{12x - 3} \)
Now we rewrite the equation: \[ 9^{12x - 3} = 9^{3x + 8} \]
Since the bases are the same, we can set the exponents equal to each other: \[ 12x - 3 = 3x + 8 \]
Next, we solve for \( x \):
-
Subtract \( 3x \) from both sides: \[ 12x - 3x - 3 = 8 \] \[ 9x - 3 = 8 \]
-
Add 3 to both sides: \[ 9x = 11 \]
-
Divide by 9: \[ x = \frac{11}{9} \]
None of the provided responses (196, \(\frac{19}{6}\), -32, \(-\frac{3}{2}\), 119, \(\frac{11}{6}\), or 9) match the solution \( x = \frac{11}{9} \). However, based on your options and calculations, please check if the equation has been transcribed correctly. If so, the solution is \( x = \frac{11}{9} \). Please let me know if there is anything else I can assist you with!